2022
DOI: 10.1021/acsapm.1c01676
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chemical Design on the Molecular Orientation of Conjugated Donor–Acceptor Polymers for Field-Effect Transistors

Abstract: Conjugated donor−acceptor polymers are a large category of cutting edge semiconductor materials with obvious advantages such as easy processing, light weight, and mechanical flexibility. By rational design of electronwithdrawing and electron-donating moieties, the intermolecular interactions between conjugated polymers can be precisely tuned, realizing the efficient control of polymer aggregation in solution and subsequent polymer packing orientation in solid states. In this Review article, the recent advances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 105 publications
0
21
0
Order By: Relevance
“…530,533,535 In these systems, introducing a less volatile solvent can change the phase separation pathway by preventing L−L demixing and allowing for sufficient time for crystallization. 530,535,605,608,609 A notable work by Franeker and Janssen et al, showed that using o-DCB as a cosolvent for PDPP5T:PCBM [70] solution in chloroform leads to finely mixed domains as compared to forming micron scale large domains when processed without cosolvents. 535 Using in situ optical techniques, the authors compared the film drying processes in solutions with 5% vs without o-DCB to find that solvent evaporation takes longer in o-DCB added chloroform solutions due to its higher boiling point as compared to the neat solvent.…”
Section: Impact Of Processing Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…530,533,535 In these systems, introducing a less volatile solvent can change the phase separation pathway by preventing L−L demixing and allowing for sufficient time for crystallization. 530,535,605,608,609 A notable work by Franeker and Janssen et al, showed that using o-DCB as a cosolvent for PDPP5T:PCBM [70] solution in chloroform leads to finely mixed domains as compared to forming micron scale large domains when processed without cosolvents. 535 Using in situ optical techniques, the authors compared the film drying processes in solutions with 5% vs without o-DCB to find that solvent evaporation takes longer in o-DCB added chloroform solutions due to its higher boiling point as compared to the neat solvent.…”
Section: Impact Of Processing Conditionsmentioning
confidence: 99%
“…530,533 For instance, Bartelt and McGehee et al investigated the effect of molecular weight of the donor polymer on BHJ morphology and device properties of PBDTTPD:PCBM [70] system. 537 Shown in Figure 36a is the TEM images of the blend films of PBDTTPD:PCBM [70] system cast from varying molecular weight (M n ) of the PBDTTPD polymer. With increasing M n of the donor polymer, the blend film morphology changes from forming large fullerene-rich domains to small fibrillar networklike domains, which resulted in a substantial enhancement in the PCE (Figure 36d).…”
Section: Impact Of Donor Polymer Assemblymentioning
confidence: 99%
“…This transition of polymer packing orientation might be explained by the competition between the molecule-molecule interactions and molecule-substrate interactions. 17,38 CF leads to a relatively weaker polymer aggregation so that the conformation of polymer chains is arranged in a relatively free way. As a result, the interactions between the polymer chains and the substrate seem more pronounced, resulting in the formation of the faceon orientation.…”
Section: Paper Nanoscalementioning
confidence: 99%
“…It is widely reported that in planar field-effect transistors, the edge-on orientation of conjugated molecules with respect to the substrate surface facilitates the charge transport, in spite of a few exceptions with a highly disordered microstructure 39 or bimodal organization. 38,40,41 To elucidate the impact of molecular orientation on charge transport for PDPP3T, field-effect transistors with a top-gate bottom-contact architecture were fabricated by using CYTOP as the dielectric layer (Fig. 5a).…”
Section: Paper Nanoscalementioning
confidence: 99%
“…For organic semiconductors, molecular orientation, which is a feature of molecular stacking in the film, plays a determinant role in the interface energy level alignment [ 42 ]. Furthermore, molecular orientation of organic semiconductors has significant influence on hole mobility, demonstrated in the field of organic field-effect transistors (OFET) [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%